Dendritic Cells as Adjuvant Therapy to Decrease Mortality for Glioblastoma Patients: Meta-Analysis - Allyssa Rahmaditta; Ervin Monica (AKSONA, 2023)
Highlight: Dendritic cells (DC) are one type of immune therapy that is being explored to improve treatment effectiveness in glioblastoma multiforme (GBM). DC was predicted to improve survival rates in GBM patients within 3 years. Effects of DC in the fifth year need to be explored to prove their. effectiveness in increasing the GBM survival rate.   ABSTRACT Introduction: Glioblastoma multiforme (GBM) is a primary neoplasm of the central nervous system with a low survival rate, requiring more effective treatment to improve long-term survival. Dendritic cell (DC) therapy is expected to reduce tumor progressivity. Obective: The purpose of this meta-analysis was to analyze the administration of DC in reducing mortality in GBM patients. Methods: A systematic literature search was conducted using the PRISMA method through the Embase database, PubMed, and the Cochrane Controlled Trials Register for relevant studies between giving DC to GBM patients with conventional therapy on the number of living patients compared to controls. Article quality was assessed using the Newcastle-Ottawa Scale and statistically analyzed using RevMan 5.4. Results: Of the 14 articles, the rates of reduction in the probability of death during the first three years after initiation of therapy were 26%, 36%, and 38%, respectively [1st-y HR: 0.74 (0.57-0.95), I2: 15%, p=0.02; 2nd-y HR: 0.64 (0.51-0.81), I2: 14%, p=0.0002; 3rd-y HR: 0.62 (0.48-0.81), I2: 0%, p=0.0004]. However, there was no difference after 5 years [HR 0.81 (0.62-1.06), I2: 0%, p=0.13].  Conclusion: The DC vaccine reduces the likelihood of death in the early years of therapy but has not been proven for long-term therapy.